2018
DOI: 10.1016/j.ajic.2018.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Patient compliance with antimicrobial drugs: A Chinese survey

Abstract: A range of factors were associated with compliance to antimicrobial therapy, including understanding of the treatment, gender, age, home address, education level, and family income.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
2
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 24 publications
5
36
2
2
Order By: Relevance
“…12 Another survey conducted in China demonstrated that nearly 87% of patients showed non -compliance with use of antibiotics and did not follow the complete course as prescribed. 13 This is in contrast with the results of our study where 26% did not follow the complete course. Possible reasons for non-compliance include fear of adverse effects caused by long term use, improvement in symptoms and complexity of the treatment.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…12 Another survey conducted in China demonstrated that nearly 87% of patients showed non -compliance with use of antibiotics and did not follow the complete course as prescribed. 13 This is in contrast with the results of our study where 26% did not follow the complete course. Possible reasons for non-compliance include fear of adverse effects caused by long term use, improvement in symptoms and complexity of the treatment.…”
Section: Discussioncontrasting
confidence: 90%
“…Possible reasons for non-compliance include fear of adverse effects caused by long term use, improvement in symptoms and complexity of the treatment. 13 In terms of practice, the role of pharmacies needs to be mentioned. They have an important role in contributing to public knowledge about appropriate antibiotic usage, as more fractions of the respondents stated that they obtained information on antibiotic use from pharmacies rather than from doctors.…”
Section: Discussionmentioning
confidence: 99%
“…1 Incorrect use and abuse of antimicrobial agents are key drivers for the spread of antimicrobial drug resistance. [2][3][4][5] Frequent and prolonged use of broad-spectrum antimicrobial agents has been associated with the emergence of antimicrobial resistance. [6][7][8] Drug therapy problem (DTP) is any undesirable event experienced by a patient related to drug therapy, which interferes with achieving the desired goals of the pharmacological intervention.…”
Section: Introductionmentioning
confidence: 99%
“…In general, these ATC markets exhibit greater rates of non-adherence and shorter treatment periods than ATC N. Two recent studies (Fernandes et al, 2014 andTong et al, 2018) place the non-adherence rates for antimicrobial therapies at greater than 57 percent. In Appendix Table 15 we find a decline in aggregate demand of 24.2 percent (Model 1).…”
Section: Heterogeneity Across Therapeutic Marketsmentioning
confidence: 99%